Allometric Models for Estimating Tree Biomass and Soil Carbon Stocks of Small Scale Plantations in Subtropical-Subtemperate Regions of Western Himalayas - Vaidya, Pratima; Verma, K. S.; Bhardwaj, S. K.; Brahmi, M. K.; Sharma, D. P.; Gupta, R. K. (Indian Forester, 2017)
Five plantations of Eucalyptus tereticornis, Populus deltoides, Quercus leucotrichophora, Eucalyptus tereticornis plus Pinus roxburghii and Quercus leucotrichophora plus Ulmus villosa were studied to access the total carbon sequestered by 24-25 year old farm plantations. Total 223 trees were enumerated and observations regarding stem, leaf, branch, above ground, below ground and total tree biomass were recorded by destructive and non destructive methods of sampling under different plantations and was converted into biomass carbon density. Per cent soil organic carbon and total soil carbon density was also determined. Mean biomass carbon and total biomass plus soil carbon density of different farm plantations varied from 150.50- 544.94 t ha-1 and followed the order: Eucalyptus tereticornis > Quercus leucotrichophora + Ulmus villosa > Populus deltoides > Eucalyptus tereticornis + Pinus roxburghii > Quercus leucotrichophora. Different generalized allometric equations were developed to estimate biomass carbon and biomass plus soil carbon stock for pure as well as mixed farm forestry plantations. For estimation of biomass and carbon in different pure and mixed stands of studied farm forestry species, diameter was taken as independent variable. Based on R2 value power function was the best fitted function for biomass carbon whereas compound function was best fitted for total biomass plus soil carbon in pure as well as mixed plantations.